Implementation of Community Based Tourism in Kebon Ayu Cultural Tourism Village, West Lombok District, West Nusa Tenggara Province - Mike Melina Janitra; Adhitya Bagus Singandaru; Mahmudah Budiatiningsih; Hulfa, Ihyana (Jurnal Penelitian Mahasiswa Pariwisata, 2024)
West Nusa Tenggara (NTB) Province, especially on Lombok Island, has a lot of tourism potential including tourist villages. There are 59 tourist villages that have been established by the NTB Provincial Government, which are spread across 5 (five) districts/cities on Lombok Island. One of the tourist villages that is currently developing is Kebon Ayu Cultural Tourism Village in West Lombok District. Kebon Ayu Cultural Tourism Village is one of the tourist villages that has won the Indonesian Tourism Village Award in 2023. Using a qualitative approach, this research aims to describe the implementation of the concept of community-based tourism in Kebon Ayu Cultural Tourism Village. Kebon Ayu Cultural Tourism Village has applied the principles of Community Based Tourism (CBT) management in managing tourism in the village. This can be seen from the involvement of the community since the mapping of the potential owned by the village to the establishment, management, and development of tourist attractions offered in the village. The impact of this involvement is the number of MSMEs formed and the opening of employment opportunities for the community in the village itself, resulting in socio-economic changes in the community. However, the lack of assistance in the form of education from stakeholders makes Human Resources (HR) related to tourism in Kebon Ayu Cultural Tourism Village still low and makes the management of tourist villages less optimal.